Stenting of a hepatic artery pseudoaneurysm rupture secondary to a celiac artery dissection - Baqir J. Kedwai, BHSc; Matthew Byrne, MD; Joshua T. Geiger, MD; Daniel J. Lehane, BA; Doran S. Mix, MD; Michael C. Stoner, MD (Journal of Vascular Surgery Cases and Innovative Techniques, 2024)
Hepatic artery (HA) pseudoaneurysm rupture is a rare and potentially lethal pathology. We present the case of a celiac artery dissection complicated by an HA pseudoaneurysm rupture that was treated successfully with endovascular stenting. The patient's postoperative course was uncomplicated, and he was further evaluated for an underlying connective tissue disorder. There is no standard treatment for a ruptured HA pseudoaneurysm, although transarterial embolization is most frequently reported. This report demonstrates that self-expanding stent grafts are effective in the emergent repair of HA pseudoaneurysm rupture.